Fitur Level Kognitif dalam Artikel Dosen: Studi Kasus pada Artikel Berlatar Bahasa dan Pengajarannya - Suhartono; Yohanes, Budinuryanta; Mintowati; Ahmadi, Anas; Adriyanto, Octo Dendi; Efendi, Rachmat; Dini Damayanti, Ajeng Mei (Nexus Publishing, 2025)
This study aims to 1) identify cognitive level features in articles written by lecturers in the field of language and its teaching based on Bloom and Anderson's taxonomy theory and 2) determine the cognitive dimensions represented in lecturers' articles. The type of research used is a descriptive analysis to describe the cognitive level in lecturers' articles on language and its teaching based on Bloom's revised taxonomy by Anderson. The data collection technique used reading comprehension and was analyzed using content analysis techniques. The results showed 1) C6 Creating was the cognitive level with the highest frequency in each feature, but the overall cognitive levels were correlated in constructing applicable, critical, reflective, and creative scientific writing patterns as knowledge and learning development and 2) The dominance of C6 indicates that lecturer articles are written at a high cognitive level, focusing on analytical, reflective, and creative aspects. This dynamic shows maturity in academic thinking by utilizing basic cognitive abilities and integrating higher-order thinking skills to develop scientific innovations. In conclusion, lecturers' articles in the field of language and its teaching have shown significant evolution in the process and cognitive dimensions.